Social Insurance Physician Burnout—Stress Factors and Coping Strategies - Corina Oancea; Anicuta Cernamoriti; Despina Mihaela Gherman; Florina Georgeta Popescu (Medicina, 2023)
Background and Objective Burnout syndrome is well-documented and highly prevalent among healthcare professionals. The literature search found studies mainly aimed at front-line medical specialties, cardiologists, or physicians working in intensive care units. Workload and work conditions favor the occurrence of burnout syndrome among social insurance physicians, with many consequences on health status and a decrease in the quality of their work. We aimed to assess the degree of vulnerability to developing burnout syndrome, factors associated with stress, and coping strategies at social insurance physicians. Materials and Methods: Social insurance physicians working in territorial services for medical assessment of work capacity from Romania participated in the study. An observational study was performed to describe the extent of the exhaustion syndrome among social insurance physicians (SIPhs). Three questionnaires were filled out by the participants: a short version of MBI-HSS to analyze the degree of burnout, an interview with specific questions for the source of stress and Brief-COPE for stress control. Brief demographic data were also collected. Data were statistically analyzed with appropriate tests using PSPP software. Results: Seventy-four physicians were included in the study. Fifty-six were females (75.7%) and twenty-eight (38%) had moderate or high burnout and cognitive distortions with depression resulting as a major side-effect (p < 0.001). Professional factors, mainly deadline pressure (p < 0.001) and high workload (p = 0.012), have emerged as contributing factors to burnout syndrome. Mental disengagement (p = 0.001), active coping (p = 0.006), and acceptance (p = 0.014) would improve stress control. Conclusion: More than two-thirds of social insurance physicians had moderate and high burnout syndrome. The development of strategies to standardize workload was identified as an important action area, along with the long-term preservation of health status and professional performance.